Clinical Outcomes in Pediatric Patients With Type 1 Diabetes With Early Versus Late Diagnosis: Analysis From the DPV Registry - Hammersen, Johanna; Tittel, Sascha R.; Kamrath, Clemens; Warncke, Katharina; Galler, Angela; Menzel, Ulrike; Hess, Melanie; Meißner, Thomas; Karges, Beate; Holl, Reinhard W. (Diabetes Care, 2024)
OBJECTIVE This study was conducted to evaluate the effects of early clinical diagnosis of type 1 diabetes by comparison of clinical parameters at diagnosis and during follow-up in patients with pediatric type 1 diabetes with early, intermediate, and late diagnosis. RESEARCH DESIGN AND METHODS In a population-based analysis, data on 14,292 pediatric patients with type 1 diabetes diagnosed between 2015 and 2019 were retrieved from the Diabetes Prospective Documentation (DPV) registry in March 2023. Patients were divided into four groups: one with diabetic ketoacidosis (DKA) at diagnosis and three with early, intermediate, or late diagnosis based on age-dependent HbA1c terciles. Laboratory-measured HbA1c values and those estimated from continuous glucose monitoring were aggregated as a combined glucose indicator (CGI). Insulin dose– adjusted CGI values <9% were defined as partial remission. RESULTS At diagnosis, patients had a median age of 9.8 years (IQR 6.8; 13.0). Three years later, patients with early diagnosis had lower CGI than patients with late diagnosis or DKA (mean [95% CI] 7.46% [7.40; 7.53] vs. 7.81% [7.75; 7.87] or 7.74% [7.68; 7.79], respectively; each P < 0.001). More patients experienced partial remission (12.6% [11.0; 14.4] vs. 9.1% [7.7; 10.7] or 8.6% [7.3; 10.0]; each P < 0.001), and 11.7% [10.2; 13.5] of patients with intermediate diagnosis were in partial remission. CONCLUSIONS Early clinical diagnosis of type 1 diabetes may be beneficial for metabolic control and remission after 3 years of follow-up. Patients diagnosed early may represent a distinct group with better resources or with a different disease biology and slower b-cell destruction, which needs further evaluation.
CRIS-Team Scopus Importer:2024-12-13